Perkembangan Motif Sineas Film Indie dalam Menghadapi Industri Film Mainstream - Ardiyono, Yoppy (Universitas Semarang, 2015)
The research aims to review to review determine the effect and its impact raised by motive - a motive the ada in the hearts period travel time history of film short against cinematographer-filmmaker as principal especially filmmakers left path (indie). The used platform theory research hearts singer adopts from theory commodification media vincent mosco. Singer helped shift theory understanding the motive filmmakers working hearts differences fundamental basis of political pressure economic happens under with demands regime. The method used is descriptive qualitative research methods. Data collection techniques through observation of the environment of an independent film live and in-depth interviews with speakers including mr. Yang prayer orangutan direct contact 'with realm of research. Coupled with study to review the literature references adding insight research. And that was concluded change appears motif among indie film cinematographer it is true the situation is closely linked to the mainstream industry, konstilasi politics, and the orientation of capitalism. Necessary their one thing is clear and systematic regulation from the government to the future movement of currents sidestream (indie) more with good operates professionally arranged, the air so that the contribution of indie cinema film land for progress can feels good to yourself indie filmmakers as well as those of its main industries.